دلالة التعليل في سورة البقرة تفسير ابن عاشور أنموذجا - احثريب, أحلام (University of Eloued جامعة الجزائر, 2020)
"هذه الدراسة الموسومة بـ: دلالة التعليل في سورة البقرة، تفسير ابن عاشور أنموذجا كان الإشكال الرئيس الذي نسعى إلى الإجابة عليه هو ما المقصود بالتعليل؟ وما هي أدواته وما مستويات توظيفه؟ وما مدى عناية ابن عاشور به في تفسيره في سورة البقرة؟ فأجابت الدراسة على ذلك من خلال ثلاثة مباحث حيث خصص الأول للتعريف بالشيخ ابن عاشور وتفسيره التحرير والتنوير وسورة البقرة ودلالة التعليل وخصص المبحث الثاني لبيان أدوات التعليل أما المبحث الثالث فقد ذكرت فيه نماذج تطبيقية من التعليل في سورة البقرة عند ابن عاشور. وتوصلت الدراسة إلى جملة من النتائج لعل أهمها تنوع أدوات التعليل في القرآن الكريم وبيان الحكمة من ذلك كما أوصت الدراسة بضرورة البحث في أساليب التعليل في القرآن الكريم والعناية بتفسير التحرير والتنوير."" The main aim of the study under the title “The significance of the reasoning in souretelbakara - Interpretation of Ibn Ashour as a model.” Is to find out what does reasoningmean?What are its tools and levels of employment? And how far does Ibn Ashur take reasoning in his consideration in interpretation of Surat Al-Baqarah? The study answered above questions through three chapters. The first chapter was devoted to the definition of Sheikh Ibn Ashur and his interpretation marked by Tahrir and Enlightenment, Surat Al-Baqarah and the significance of the reasoning. The second one was about reasoning tools. In the third chapter, I mentioned applied models of reasoning in Surat Al-Baqara according to Ibn Ashur. The study reached a set of resultsperhaps the most important of them is the diversity of the reasoningtools in the Holy Quran. The study also recommended the necessity of researching the methods of reasoning in the Holy Qur’an and paying attention to the interpretation of Tahrir and enlightenment book. "
مذكرة ماستر تخصص لغة ودراسات قرآنية
Keywords: التعليل، سورة البقرة، ابن عاشور، التحرير والتنوير.; Reasoning, Surat Al-Baqara, Ibn Ashur, Tahrir and Enlightenment